2020
DOI: 10.7759/cureus.12034
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Efficacy of Gabapentin Versus Levodopa-C for the Treatment of Restless Legs Syndrome in End-Stage Renal Disease on Hemodialysis Patients

Abstract: Objective: We aimed to compare the efficacy of gabapentin and levodopa-c for the symptoms of restless leg syndrome in patients of end-stage renal disease (ESRD) undergoing maintenance hemodialysis therapy. Methods: In this observational, cross-sectional study, patients of ESRD on hemodialysis with restless leg syndrome were included after assessment of symptoms and quality of sleep before the treatment by completing two questionnaires: the International Restless Leg Syndrome Study Group (IRLSSG) questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…However, after the second intervention, although the reduction in RLS score was higher in the gabapentin group, there were no statistically significant difference between the two groups. In this regard, the results of the study by Ali et al, who compared gabapentin with levodopa, in line with the present study, showed a greater effect of gabapentin on reducing the RLS score [16]. In the study by Garcia-Borreguero et al, the RLS score was improved in the group that took gabapentin compared to the placebo group [25] and consistent with the present study, gabapentin caused a more reduction in the RLS score.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, after the second intervention, although the reduction in RLS score was higher in the gabapentin group, there were no statistically significant difference between the two groups. In this regard, the results of the study by Ali et al, who compared gabapentin with levodopa, in line with the present study, showed a greater effect of gabapentin on reducing the RLS score [16]. In the study by Garcia-Borreguero et al, the RLS score was improved in the group that took gabapentin compared to the placebo group [25] and consistent with the present study, gabapentin caused a more reduction in the RLS score.…”
Section: Discussionsupporting
confidence: 91%
“…This syndrome causes chronic insomnia and daytime sleepiness, and therefore affects the patients' quality sleep [14,15]. Patients with moderate to severe RLS may sleep less than 5 h at night [16].…”
Section: Introductionmentioning
confidence: 99%
“…Also, in an observational study of 26 patients with RLS, both levodopa and gabapentin significantly enhanced RLS symptoms. However, gabapentin was better in improving the quality of sleep with fewer chances of rebounding and augmentation 133…”
Section: Methodsmentioning
confidence: 93%
“…However, gabapentin was better in improving the quality of sleep with fewer chances of rebounding and augmentation. 133 Dopaminergic Drugs: dopamine agonists are widely used for treating RLS symptoms. The only dopaminergic drugs approved by the FDA include ropinirole, pramipexole, and rotigotine.…”
Section: Pharmacological Optionsmentioning
confidence: 99%
“…In the present study, gabapentin was the most effective pharmacological intervention in reducing RLS symptoms. The gabapentin dosage in the included studies was 100–300 mg after dialysis sessions [ 8 , 11 , 37 ]. Although the treatment dosage was within the recommended range, gabapentin-related adverse events and patient dropouts were still reported [ 37 ].…”
Section: Discussionmentioning
confidence: 99%